DARI SUPERVISI KE MUTU: PERAN STRATEGIS KEPALA SEKOLAH DAN GURU DALAM IMPLEMENTASI MERDEKA BELAJAR MENUJU INDONESIA 2045 - Pipit Athyana Isniasih; Anam Sutopo; Sofyan Anif (STKIP Subang, 2026)
The transformation of education in the Merdeka Belajar era demands improvements in educational quality that emphasize student-centered learning, however challenges remain in its implementation, particularly regarding the roles of school principals and teachers. This study aims to analyze the roles of school principals and teachers in optimizing educational quality to support the vision of Golden Indonesia 2045. The research employed a qualitative descriptive approach using document analysis of employee performance targets and teacher performance evaluations. The results show that all teacher performance indicators reached 100% and work behavior was categorized as appropriate, indicating optimal learning implementation and a positive work culture. The discussion reveals that effective school leadership, continuous supervision, and adaptive teacher competence are key factors in improving educational quality. In conclusion, the synergy between school principals and teachers plays a significant role in supporting the success of Merdeka Belajar and achieving the vision of Golden Indonesia 2045.